L'enjeu de l'apprentissage performant du transport fluvial par les organisations logistiques : quels enseignements pour l'action publique ? - Ludovic Vaillant (Développement Durable et Territoires)
Control of the growth of road transport has become a major societal issue for many years. Several public policies have been conducted at different political levels without succeeding to reverse the trend. The recurrent failure of these policies encourages to reconsider it's standards of action and to better understand the system on which they are supposed to act. The article, by adopting a non deterministic point of view, proposes to clarify the mechanisms of evolution of transport contracts, and particularly the transfer towards the use of waterways. The evolutionist and institutionalist approach, which bases the analysis, leads to demonstrate that increased and perennial use of waterway transport involves a radical evolution of the paradigms that underpin the decisions of logistic organizations. Moreover, this evolution should be supported by institutional dynamics.